The conquest of land by the Amphipoda (Senticaudata, Talitroidea) explained by global tectonics and vicariance - Myers, Alan (Zootaxa, 2022)
The Talitroidea originated from a marine ancestor in the amphipod family Hyalidae that colonised marshy land flooded occasionally by the sea. From there, some descendants migrated inland along river catchments, as their terrestrial adaptations evolved, becoming riparian. Over time they colonised moist habitats in fields and forests. The superfamily Talitroidea comprises all known terrestrial amphipods and it has an almost worldwide distribution, but families have discrete distributions. Because all amphipods release fully formed young and have no dispersive phase in their life history, their potential for dispersal is extremely limited. Terrestrial talitroids are particularly constrained on a global scale, because their adaptations for terrestrial life prevent them from crossing seas or oceans. It has been hypothesised that Talitridae living on marine shores might traverse oceans on rafts of detached wrack. Support for this might be the fact that beach hoppers are the most widely distributed of the Talitroidea. However, they have been shown to abandon floating objects actively and several attempts to explain specific cases of talitrid distributions by implicating rafting have been falsified. The broad distributions of Talitroidea across the globe can be explained parsimoniously only by vicariance. The family Arcitalitridae is, with one exception, endemic to Australasia and South Africa, which have been separated from one another since the late Jurrasic c.150Ma. The exception is provided by two genera in Indochina, which probably arrived in Laurasia when India, which had been part of east Gondwana, accreted to Laurasia in the Miocene. However, terranes separated from the margins of Gondwana in the late Triassic-early Jurrasic and then accreted as allochthonous terranes to Laurasia, so the possibility of arcitalitrids arriving in Laurasia at that time, cannot be excluded. The family Makawidae, which is endemic to Zealandia and Tasmania, probably attained it’s current distribution through the expansion of the Tasman Sea in the Cretaceous.